Morphology versus molecules: The phylogenetic relationships of Sepsidae (Diptera: Cyclorrhapha) based on morphology and DNA sequence data from ten genes - Feng-Yi Su, K. (2014)
10.1111/j.1096-0031.2008.00222.x